The value of c-kit mutational analysis in a cytokeratin positive gastrointestinal stromal tumour. Issue 9 (26th August 2005) - Rossi, G; Sartori, G; Valli, R; Bertolini, F; Bigiani, N; Schirosi, L; Cavazza, A; Luppi, G
Abstract : The expression of cytokeratins in gastrointestinal stromal tumours (GISTs) is rare and may lead to diagnostic confusion when it occurs. This report describes a metastatic GIST that stained strongly for cytokeratins, CD117, and CD34 in a patient who was previously diagnosed with gastric epithelioid angiosarcoma. A review of both tumours showed the same histological and immunohistochemical profiles, and c-kit molecular analysis revealed an insertional mutation at codon 558 of exon 11 in both tumours. Thus, pathologists should be aware that GISTs can occasionally express cytokeratins, and that c-kit mutational investigations may have a key diagnostic role and may prevent diagnostic mistakes that could have important clinical implications.